Editor's preface - Zasiekin, Serhii (East European Journal of Psycholinguistics, 2015)
Language is an indispensable part of our life. It functions practically in all spheres of human activity. We hear it, we use it, we process it every day, cognize things through it. Still, some questions as to its nature remain to be answered. As Noam Chomsky noted, “The most fundamental one, surely, is: What is language? To the extent that we have some grasp of this, we can proceed to study other significant questions. It would not suffice to say that it is used to communicate (among other uses)” (Chomsky 2015:91). Therefore, the factors determining the nature of language in humans do not belong exclusively to theoretical linguistics. Language in communicative interaction is an object of psycholinguistics (Arabski 2007:9). This second journal number of Volume 1 presents original manuscripts by authors from Iran, Italy, Sweden, Ukraine, who made an attempt to shed light on basic issues of theoretical and applied psycholinguistics. The majority of the scholars whose articles are collected here capably discussed key contemporary matters relating to the interdependence of language and individual behavior.The contributions focus on theoretical psycholinguistics (Olena Savchenko), translator’s creativity (Nataliya Dyachuk), academic and second/foreign language acquisition issues (Ehsan Amini, Javad Ahmadi Fatalaki, Iya Hordiyenko-Mytrofanova, Yana Kaznacheyeva, Oleksandr Kapranov, Meysam Mirzaee), psychology of language and speech (Maryna Orap), clinical psycholinguistics (Larysa Zasiekina), ethno-psycholinguistics (Amelia Manuti, Giuseppe Mininni, Inna Tarasiuk, Altomare Enza Zagaria), text and discourse analysis (Diana Kalishchuk, Nataliya Kashchyshyn, Larysa Makaruk, Anastasiia Odintsova), cognitive phono-semantics (Oleksandr Lavrynenko). Finally, Taras Shmiher in his two brilliant reviews sought to bridge translation studies and cognitive linguistics by assessing three books on translation studies published by Polish and Spanish scholars.Hopefully, the articles of this volume can offer at least a few psycholinguistic solutions to the problem of understanding of what language actually is.        ReferencesArabski, J. (2007). Preface. In: Challenging Tasks for Psycholinguistics in the New Century. (p. 9), Janusz Arabski, (ed). Katowice: University of Silesia.Chomsky, N. (2015). Some core contested concepts. Journal of Psycholinguistic Research, 44, 91–104.